Epstein-Barr virus-induced autoimmune responses. II. Immunoglobulin G autoantibodies to mimicking and nonmimicking epitopes. Presence in autoimmune disease. - J H Vaughan; M D Nguyen; J R Valbracht; K Patrick; G H Rhodes (The Journal of Clinical Investigation, 1995)
During infectious mononucleosis, IgM autoantibodies are generated to a protein, p542, which contains a glycine-rich 28-mer epitope cross-reactive with the Epstein-Barr nuclear antigen-1 through Epstein-Barr nuclear antigen-1's glycine/alanine repeat. In normal individuals it is uncommon to find IgG anti-p542, but among patients with progressive systemic sclerosis, systemic lupus erythematosus, and ulcerative colitis high IgG anti-p542 (> 3 SD above the mean of normal 20-50 yr controls) occurred frequently. Lesser elevations occurred in Sjögren's syndrome, rheumatoid arthritis, ankylosing spondylitis, and Crohn's disease, but none with chronic hepatitis B infection. The reactive epitopes on p542 were mapped with deletion mutants, which indicated that the glycine-rich 28-mer was the major antigenic determinant, with lesser antibody responses to other epitopes. We conclude that normally there is an inability to generate IgG autoantibodies to the cross-reactive (mimicking) epitope of the p542 host protein, but that this inability is overcome in a proportion of patients with autoimmune disease. We conclude also that non-cross-reactive autoepitopes exist on p542 protein, to which IgG autoantibodies can commonly be formed in autoimmune disorders. The mechanisms responsible for the latter must involve different mechanisms than those responsible for autoantibodies to the mimicking epitope. Images